Leptin as immune mediator: Interaction between neuroendocrine and immune system. (January 2017) - Procaccini, Claudio; La Rocca, Claudia; Carbone, Fortunata; De Rosa, Veronica; Galgani, Mario; Matarese, Giuseppe
Abstract: Leptin is an adipocyte-derived hormone/cytokine that links nutritional status with neuroendocrine and immune functions. Initially described as an anti-obesity hormone, leptin has subsequently been shown to exert pleiotropic effects, being also able to influence haematopoiesis, thermogenesis, reproduction, angiogenesis, and more importantly immune homeostasis. As a cytokine, leptin can affect both innate and adaptive immunity, by inducing a pro-inflammatory response and thus playing a key role in the regulation of the pathogenesis of several autoimmune/inflammatory diseases. In this review, we discuss the most recent advances on the role of leptin as immune-modulator in mammals and we also provide an overview on its main functions in non-mammalian vertebrates. Highlights: Leptin regulates function of macrophages, dendritic cells, NK cells, neutrophils, eosinophils and basophils. Leptin increases and sustains CD4 + T cells function. Leptin is a negative signal for Treg cells function. Leptin regulates function of macrophages, dendritic cells, NK cells, neutrophils, eosinophils and basophils.